Discrete shortest paths on smooth surface representations - Kanai, T.; Ohtake, Y. (2008 IEEE International Conference on Shape Modeling and Applications, 2008)
We introduce an algorithm for computing discrete shortest paths on smooth surface representations. For given source and target points on a surface, an initial shortest path is computed by using the Dijkstra's algorithm. Based on such an initial curve, locally-refined discrete paths are repeatedly calculated so as to get more accurate shortest path. Our algorithm is simple, easy to implement and much fast because it requires only the Dijkstra's algorithm to compute the path. Our algorithm is a versatile approach for a wide variety of smooth surface representations.